The Role of Social Networks in Cultural Assimilation - Thierry Verdier; Yves Zenou (Institute for the Study of Labor (IZA), 2015)
We develop a model where, in the first stage, minority individuals have to decide whether or not they want to assimilate to the majority culture while, in the second stage, all individuals (both from the majority and the minority group) embedded in a network have to decide how much effort they exert in some activity (say education). We show that the more central minority agents are in the social network, the more they assimilate to the majority culture. We also show that denser networks tend to favor assimilation so that, for example, it is easier to assimilate in a complete network than in a star-shaped network. We show that the subgame-perfect equilibrium is not optimal because there is not enough activity and assimilation. We then endogeneize the network and show under which condition the ethnic minorities either assimilate to or separated themselves from the majority group.
Keywords: D85; J15; Z13; 330; network centrality; ethnic minorities; majority individuals; assimilation; network formation